(3eSFhdjI GdfGbd GdHQi ddCTNGU ai GdbGfhf Gdjefi (B: s (3OQGSI ebGQfI (B/ s - (3YHOGddg eMeO jMji GdYdais; (3SejMI eUWai GdbdjhHis; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2020)
(3JfGhdJ GdOQGSI ehVhY eSFhdjI GdfGbd GdHQi ddCTNGU ai GdbGfhf Gdjefi (B"(3OQGSI ebGQfI(B" (3h gh ef Cge ehVhYGJ YbO fbd GdCTNGU(B: (3h bSeJ GdOQGSI (B((3deHMK JegjOi(B) (3NUU dOQGSI GdedGeM GdYGeI dYbO Gdfbd GdHQi ddCTNGU(B: (3h HGHjf QFjSjjf(B: (3NUU GdChd deGgjI eSFhdjI GdfGbd GdHQi ddCTNGU(B: (3h GdKGfi dBKGQ eSFhdjI GdfGbd GdHQi ddCTNGU(B. (3h NdUJ GdOQGSI Gdi EVaGA GdeTQYGf Gdjefi h GdeUQi CMcGeG NGUI dJbQjQ eSFhdjI GdfGbd GdHQi ddCTNGU NQhLG Ydi GdbhGYO GdYGeI ddeSFhdjI GdhGQOI ai GdbGfhf GdeOfi(B: (3ef MjK bjGe eSFhdjI GdfGbd GdHQi ddCTNGU h BKGQgG(B: (3h Pdc HZjI JhajQ CcHQ bOQ eecf ef GdMeGjI ddQGcH h ef ai Mceg ai ehGLgI GdfGbd(B: (3h eQO Pdc gh WHjYI GdQGcH GdPi jYO GdWQa GdCVYa ai GdYbO(B: (3h CUHMJ eSFhdjI GdfGbd GdHQi ddCTNGU JLGg GdQGcH eSFhdjI YbOjI eaJQVI JbY HeLQO hbhY GdCVQGQ Ydi GdQGcH CKfGA YedjI Gdfbds
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdJLGQj, (B2020s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B: (3UaMI (B322-340s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdJLGQjs; (3GdfGbd GdHQj ddCTNGU s; (3GdbGfhf Gdjefj s; (3YbO Gdfbd GdHQj ddCTNGU s; (3GdWHjYI GdbGfhfjI deSFhdjI GdfGbd GdHQjs; (3GdfGbd GdHQjs; (3GdJRGeGJ GdfGbds; (3GdEYaGA ef GdeSFhdjIs; (3GdCVQGQ GddGMbI HCeJYI GdQGcH s; (3OYhi eSFhdjI GdfGbd GdHQj ddCTNGU s; (3GdJYhjVs; (3GdQGcHs; (3aYd GdZjQs; (3GdbhI GdbGgQI s; (3GdCSHGH GdGJaGbjI s; (3GdCSHGH GdbGfhfjI s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdJLGQjs